Retinal ganglion cells projecting to the accessory optic system in optokinetic blind albinotic rats are direction‐selective. (3rd April 2014) - Krause, Martin; Distler, Claudia; Hoffmann, Klaus‐Peter
Abstract The optokinetic deficits in albinotic rats and ferrets are caused by the loss of direction selectivity in the accessory optic system (AOS). However, the underlying mechanisms for this loss are still not clear. Here we tested the hypothesis that, in albino rats, the retinal input to the AOS lacks direction selectivity and, as a consequence, neurons in the AOS are direction non‐selective. We investigated ON‐center direction‐selective retinal ganglion cells, the major input to the AOS, in pigmented Long Evans and albino Wistar rats using extracellular in vitro patch‐clamp techniques. To visualise putative AOS‐projecting direction‐selective ganglion cells, we retrogradely labeled them by injection of the infrared‐sensitive dye indocyanine green into the medial terminal nucleus of the AOS. The present study is the first to present physiological evidence for retinal ON‐center direction‐selective ganglion cells in rat. Our results show that, in albinotic and pigmented rats, ON‐center retinal ganglion cells projecting to the AOS are similarly direction‐selective, suggesting that the optokinetic deficit must be caused by the abolition of direction selectivity in the AOS itself.